Analisis Strategi Pemasaran Dalam Meningkatkan Volume Penjualan Produk Perusahaan PT. Adi Citra Anggana Kepada PT. Vale Indonesia - Bonifasius Tonapa; Amir Jaya; Agustinus Ba’ka (Paulus Journal of Accounting (PJA), 2024)
Every company must know the environmental changes that occur because it is very important to determine the strategy that the company will set to achieve its goals. For this reason, careful planning is needed in achieving these goals, the easier an environment changes, the greater the impact on strategy implementation, so this is very important in determining marketing strategies. PT Adi Citra Anggana is one of the companies engaged in hose fabrication and supplier in Indonesia. at PT Vale Indonesia PT Adi Citra Anggana is still experiencing sales problems, namely the instability of product sales, therefore this study aims to determine marketing strategies and utilization of opportunities to increase sales volume, this research uses a qualitative design that produces descriptive data from speech or writing from the behavior of PT Adi Citra Anggana itself and uses SOAR analysis to analyze data obtained from interviews and secondary methods. To deal with this, PT Adi Citra Anggana carried out a marketing strategy by choosing to formulate the intended market using segmentation, targeting and positioning and developing a marketing mix or 7P marketing mix consisting of four main elements, namely product, price, distribution, promotion and 3 additional elements, namely people, human, physical facilities from this analysis obtained strategies including promotion, approach and establish good relationships with all managers of each department as well as with the leaders of contracting companies at PT. Vale Indonesia, conducting market research on the needs of hose, adapter and fire slevee products, increasing customer trust by issuing new products according to consumer input with the best superior quality, maximizing every service and service by providing a good response, developing human resources by conducting marketing training to employees, management makes monthly and annual sales targets.